Perbandingan Metode Bina Marga Dan Metode PCI (Pavement Condition Index) Dalam Penilaian Kondisi Perkerasan Jalan (Studi Kasus : Simpang Lago - Simpang Buatan) - Copricon, Deby Elfi; Wibisono, Gunawan; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
There are methods that can be used to evaluate pavement conditions, such as Bina Marga and PCI (Pavement Condition Index) methods. In the Bina Marga method, the determination of road condition values are done by summing numbers and values of damage conditions, while PCI method is based on type, rate and area of distresses. This study attempts to compare the two methods in determining a road segment pavement condition (i.e. segment of Simpang Lago to Simpang Buatan, Riau). The road segment was divided into 6 sub segments. Primary data obtained from field surveys and secondary data were used. The priority of pavement maintenance actions was ranked from 0 to 7 for Bina Marga method, and from 0 to 100 for PCI method. The comparative analysis showed different results between the two methods in terms of pavement condition values and maintenance actions. Based on each method’s pavement condition rank, the condition values of the sub segments were 9, 10, 10, 10, 9, 10 for Bina Marga method which all needed for routine maintenance. The PCI method gave larger range of condition values, i.e. 82, 79, 57, 28, 28,and 27.keywords :pavement condition,bina marga, PCI